2014
DOI: 10.1016/j.jbiomech.2014.10.030
|View full text |Cite
|
Sign up to set email alerts
|

Is early osteoarthritis associated with differences in joint congruence?

Abstract: Previous studies suggest that osteoarthritis (OA) is related to abnormal or excessive articular contact stress. The peak pressure resulting from an applied load is determined by many factors, among which is shape and relative position and orientation of the articulating surfaces or, referring to a more common nomenclature, joint congruence. It has been hypothesized that anatomical differences may be among the causes of OA. Individuals with less congruent joints would likely develop higher peak pressure and thu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…We considered this assumption to be reasonable since Koff et al has previously shown that the cartilage in early osteoarthritic (stage I) and even stage II and III osteoarthritic TMC joints exhibited less than 10 % variation in cartilage thickness across quadrants [5]. Similarly, Conconi, Halilaj [29] assumed that the subchondral bone was a reasonable measure for calculating joint congruence distribution in the neutral position using a contact based congruence measure. In healthy TMC cartilage, the mean thickness is less than 1 mm, and variation from the mean is small enough to not significantly affect the outcomes of a force controlled FE analysis.…”
Section: Discussionmentioning
confidence: 99%
“…We considered this assumption to be reasonable since Koff et al has previously shown that the cartilage in early osteoarthritic (stage I) and even stage II and III osteoarthritic TMC joints exhibited less than 10 % variation in cartilage thickness across quadrants [5]. Similarly, Conconi, Halilaj [29] assumed that the subchondral bone was a reasonable measure for calculating joint congruence distribution in the neutral position using a contact based congruence measure. In healthy TMC cartilage, the mean thickness is less than 1 mm, and variation from the mean is small enough to not significantly affect the outcomes of a force controlled FE analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of size might play an important role in the mechanical etiology of CMC joint pathology, such as osteoarthritis (OA). Recent studies have shown that the articular surface is no different between men and women after scaling for size (Conconi et al, 2014; Halilaj et al, 2014b; Marzke et al, 2012). To the author’s knowledge, this is the first report suggesting that the shape of the entire CMC joint bones between men and women are similar.…”
Section: Discussionmentioning
confidence: 99%
“…The sexual dimorphism of the CMC joint bones is believed to play an important role in this discrepancy (Ateshian et al, 1992; Kovler et al, 2004; North and Rutledge, 1983; Xu et al, 1998). Prior studies investigating sex differences in morphology of the CMC joint bones have been focused on the articular surface morphology and range in complexity from simple descriptive classification (Van Nortwick et al, 2013), to measurement of curvature, through the use of dial indicators (North and Rutledge, 1983) and 3D models obtained through stereophotogrammetry (Ateshian et al, 1992; Xu et al, 1998), segmentation of CT images (Conconi et al, 2014; Halilaj et al, 2014b), and laser scanning (Kovler et al, 2004; Marzke et al, 2012). In contrast to previous findings, recent CT-imaging-based studies have found no sex differences in the articular shape of the CMC joint (Conconi et al, 2014; Halilaj et al, 2014b; Marzke et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In this paper the investigation of contact disfunctions was performed by considering the joint congruence theory, based on the elastic foundation contact model (EFCM) by Winkler and on the clever intuition of Conconi et al [16][17][18].…”
Section: Joint Congruence and Contact Modelmentioning
confidence: 99%
“…According to Conconi et al [16][17][18], joint congruence measurements can be obtained by analysing the geometrical relationships of the contact surfaces of the joint. When combined with the EFCM, congruence measurements provide information about the ratio between the applied resultant load on the joint and the peak pressure.…”
Section: Joint Congruence and Contact Modelmentioning
confidence: 99%